Low cost ceramic membrane for treatment of oily effluents (Research, Society and Development, 2021)
Water pollution is one of society's greatest challenges. Several contaminants come into contact with large volumes of water, compromising its quality parameters. Among the contaminants, the large number of industrial activities responsible for the generation of oily effluents stand out for their impacts on the environment, affecting, for example, the maintenance of marine life and the productivity of soils. Among the treatment techniques, the use of ceramic membranes stands out for its high efficiency in the treatment of oily effluents, mainly oil-water emulsions. In line with the development of green chemistry, associated with low cost, this work aims to prepare ceramic membranes using brasgel clay, abundant in the state of Paraíba, The clay was characterized using the techniques of X-Ray Diffraction, Energy Dispersive X-ray Fluorescence Spectroscopy, Infrared Spectroscopy, Physical Nitrogen Adsorption, Thermal Analysis. The membrane was obtained through the uniaxial dry compaction technique and sintered at 650 °C, with water flow and permeate flow being carried out to obtain the membrane rejection coefficient. The results obtained indicate that the brasgel clay has all the characteristics corresponding to smectite, and the low cost membrane had a high rejection, 100.00 %, which makes it viable for the treatment of oil-water emulsions.